A Water Experiment Benchmark to Evaluate Numerical Models for the Motion of Particles in Continuous Casting Tundish. Issue 1 (28th September 2016) - Vakhrushev, Alexander; Wu, Menghuai; Ludwig, Andreas; Nitzl, Gerald; Tang, Yong; Hackl, Gernot; Wincor, Raimund
Abstract : This paper presents a water experiment benchmark for evaluation of the numerical models for the particle motion in a continuous casting tundish. The particles are optically tracked in the model tundish and additionally are captured by instrumented wooden frames at the water surface. In the meantime, an attempt is made to simulate the water flow and motion of the particles by using the Eulerian–Lagrangian approach. It is shown that for the experiment with large particles ( ϕ 3.5 mm) the experimentally determined distribution of the particles as captured by the wooden frames can be numerically simulated, but for the small particles (with a diameter distribution between 50 and 600 μm) there is still relative large mismatch between the simulation and the experiment. Some modeling options and parameters must be tuned carefully. This raises concern for the future application of the models in real engineering process where experimental calibration and evaluation are not possible. Therefore, the goal of this paper is to (i) call contributions from researchers to propose their models and evaluate them against the same benchmark; (ii) verify the agreement of the numerical solutions obtained by different contributors, and (iii) comment on further improvements and modifications to the existing models. Abstract : A water experiment benchmark is presented to evaluate the numerical models for the particle motion in a continuous casting tundish. The particles are optically tracked and additionally are captured by instrumented wooden frames at the water surface. A simulation of water flow and motion of the particles by using the Eulerian–Lagrangian approach is performed.